AUDIT INFORMASI PADA UPT BAHASA UNIVERSITAS NUSA CENDANA - Yosefina K.I.D.D Dhae (Universitas Nusa Cendana, 2021)
This research aims to present the results of the study about the information management practice through conducting an Information Audit (IA). The research was conducted at Language Centre of Nusa Cendana University in Kupang – East Nusa Tenggara. The information audit was conducted to examine (1) the existing information resources available to the staf of Language Centre and (2) to find out the information problems faced by the staf in the Language Centre.Case study research methodology was applied with document analysis, questionnaire and interviews were used for data collection. All data were analysed manually, where data from questionnaire was generated directly to Microsft Excel to create a list of information resources. Further, Thematic analysis method was used to analyse the interview data to find general themes of information problem. Study found that documents, websites,and information system were the information resources used by the staf. While, People, Timeliness, and Technology were the main information problems faced by the staf. This study recommended that Language Centre must create an information policy, conduct a digital literacy or computer training for the employees to improve their performance in using technology and create an integrated information system. It is also important that university can also conducting information audit for whole units, faculties in Undana in order to create a general information policy for university to have a better information management practice as well as to help the university to achieve its strategic goals. Keywords: Information Management, Information Audit, Information Resources, Case Study, Information problems.